2022
DOI: 10.1186/s13102-022-00560-9
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian male water polo players’ body composition can predict specific playing positions and highlight different nutritional needs for optimal sports performance

Abstract: Background Water polo is unique among aquatic—and generally other—sports as it includes cyclic elements typical in swimming and acyclic elements occurring mainly in ball games. Moreover, water polo demands high level of technical and tactical skills. Players need an optimal nutritional and physical condition to achieve high athletic performance, which is to a great extend influenced by nutritional habits. We aim to highlight possible shortfalls in players’ nutritional intake in relation to posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our previous study, we found that elite male water polo players consumed less protein than recommended in the guidelines [ 15 ]. In this current study, we conducted a 31-day observational period to examine how a short-term diet of plant-based vegan protein affected muscle development in elite water polo players.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that elite male water polo players consumed less protein than recommended in the guidelines [ 15 ]. In this current study, we conducted a 31-day observational period to examine how a short-term diet of plant-based vegan protein affected muscle development in elite water polo players.…”
Section: Introductionmentioning
confidence: 99%